2008
DOI: 10.1254/jphs.fp0071224
|View full text |Cite
|
Sign up to set email alerts
|

Possible Role of Extracellular Nucleotides in Ectopic Ossification of Human Spinal Ligaments

Abstract: Abstract. To reveal the involvement of extracellular nucleotides in the ossification process in ossification of the posterior longitudinal ligament of the spine (OPLL), the mRNA expression profiles of P2 purinoceptors, mechanical stress-induced ATP release, and ATP-stimulated expression of osteogenic genes were analyzed in ligament cells derived from the spinal ligament of OPLL patients (OPLL cells) and non-OPLL cells derived from the spinal ligaments of cervical spondylotic myelopathy patients as a control. T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
10
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(11 citation statements)
references
References 40 publications
1
10
0
Order By: Relevance
“…The observation that OPN was significantly up‐regulated by ATPγ‐S in the presence of 5.35 mM Ca 2+ suggests that signaling pathways associated to purinergic receptors and the calcium messenger system regulate bone matrix synthesis and mineralization. Interestingly, up‐regulation of OPN expression in osteoblastic cell monolayer cultures has also been shown by mechanical stress as compressive forces, which also stimulates ATP release from these cells [Rath et al, ; Sawada et al, ]. Our findings show increased ALP activity after cell stimulation with low concentration of UTP (10 µM) or high concentration of UDP (100 µM) in osteogenic medium containing 5.35 mM Ca 2+ , suggesting that these conditions promote osteogenic differentiation.…”
Section: Discussionsupporting
confidence: 73%
“…The observation that OPN was significantly up‐regulated by ATPγ‐S in the presence of 5.35 mM Ca 2+ suggests that signaling pathways associated to purinergic receptors and the calcium messenger system regulate bone matrix synthesis and mineralization. Interestingly, up‐regulation of OPN expression in osteoblastic cell monolayer cultures has also been shown by mechanical stress as compressive forces, which also stimulates ATP release from these cells [Rath et al, ; Sawada et al, ]. Our findings show increased ALP activity after cell stimulation with low concentration of UTP (10 µM) or high concentration of UDP (100 µM) in osteogenic medium containing 5.35 mM Ca 2+ , suggesting that these conditions promote osteogenic differentiation.…”
Section: Discussionsupporting
confidence: 73%
“…Additionally, it seems clear that multiple growth factors, 4,[9][10][11]35,40,41 cytokines, 23,42 and transcription factors 1,29 are involved in the pathogenesis, inheritance, and development of OPLL. Multiple polymorphisms in multiple genes of multiple bone modulating proteins have been linked to OPLL.…”
Section: Discussionmentioning
confidence: 99%
“…40 Horikoshi et al 4 demonstrated that an alternative TGF gene, TGFB3, was found to have a significant association to OPLL (while many other previously implicated candidate genes, such as COL11A2, did not show significant association). Other growth factors, cytokines, and genes that have been shown to have increased expression or different polymorphisms between patients with OPLL and those without included purinoceptors, 29 osteopontin, 1 CTGF/Hcs24, 42 the estrogen receptor, and interleukin-1.…”
Section: Cytokines and Transcription Factorsmentioning
confidence: 99%
“…47 The P2Y1 purinoceptor subtypes, intensively expressed in OPLL cells, responded to mechanical stress-induced extracellular adenosine triphosphate, which stimulated OPLL progression. 110 Frequent consumption of pickles, nondaily consumers of rice, 100 family history of myocardial infarction, high body mass index at age 40, long working hours, and working night shifts 58 were associated with increased risk of OPLL. On the other hand, frequent consumption of chicken and soy products 100 and good sleeping habits (6-8 hours/night) in the prime of life may decrease the risk of OPLL.…”
mentioning
confidence: 99%